Ennio Candotti (1942 – 2023) - Fabris, Júlio (Cadernos de Astronomia, 2024)
Text in honor of Ennio Candotti, who passed away on December 6, 2023. Ennio retired as a professor at the Federal University of Espírito Santo and was one of the most active and instigating person within the academic world in Brazil.